The protective effect of autophagy on ischemia/reperfusion-induced hearing loss: implications for sudden hearing loss. Issue 17 (6th December 2017) - Yang, Haidi; Pang, Jiaqi; Xiong, Hao; Sun, Yingfeng; Lai, Lan; Chen, Suijun; Ye, Yongyi; Yang, Zhengfei; Zheng, Yiqing
Abstract : The present study aimed to determine the effects of ischemia/reperfusion (IR) injury for the carotid system on hearing, particularly, the role of autophagy in this process. Sixty-three Sprague-Dawley rats were divided randomly into three groups: sham surgery animals (S), temporary carotid artery occlusion (ischemia) for 30 min (I30), and temporary carotid artery occlusion for 60 min (I60). Auditory brainstem response measurements were performed on mice. After 72 h of reperfusion, the microcirculation was measured in mice after ischemia injury. Immunofluorescence was used to examine the expression of caspase-3 and light chain 3B in the cochlear sections. Temporary carotid artery occlusion lasting for 30 (I30) or 60 min (I60) caused significant hearing loss in the ischemia phase. Following a recovery during the postreperfusion phase, the temporal threshold shift occurred in the I30 group, whereas a permanent threshold shift occurred in the I60 group. Moreover, both microcirculation and autophagy affected hearing 24 h after reperfusion, whereas at 72 h, autophagy works as an intrinsic cellular process that protects against death from the IR effect. These results suggest that the sooner the reperfusion, the better the hearing recovery. In conclusion, autophagy promotes cell survival in the cochlea; however, excessive IR damage counteracts the beneficial potential of autophagy protection and leads to a permanent threshold shift.